Suboptimal Control Strategies for Finite-Time Nonlinear Processes with Input Constraints. (17th November 2013) - Rivadeneira, Pablo S.; Adam, Eduardo J.
Abstract : Novel techniques for the optimization and control of finite-time processes in real-time are pursued. These are developed in the framework of the Hamiltonian optimal control. Two methods are designed. The first one constructs the reference control trajectory as an approximation of the optimal control via the Riccati equations in an adaptive fashion based on the solutions of a set of partial differential equations called theα andβ matrices. These allow calculating the Riccati gain for a range of the duration of the processT and the final penalizationS . The second method introduces input constraints to the general optimization formulation. The notions of linear matrix inequalities allow us to recuperate the Riccati gain as in the first method, but using an infinite horizon optimization method. Finally, the performance of the proposed strategies is illustrated through numerical simulations applied to a batch reactor and a penicillin fed-batch reactor.